2010
DOI: 10.3892/or_00000755
|View full text |Cite
|
Sign up to set email alerts
|

Sorbitol dehydrogenase expression is regulated by androgens in the human prostate

Abstract: Abstract.Sorbitol is an intermediate in the polyol pathway, which converts from glucose to fructose by sorbitol dehydrogenase (SORD). Androgens are essential for the development of prostate cancer. We studied castration-induced gene expression changes in the human prostate using the GeneChip array, and identified SORD as being androgen-regulated in the human prostate. A putative androgen-responsive regulatory region at the SORD 5' promoter was identified using promoter deletion constructs in a luciferase repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…Ortiz et al detected a significant reduction of fructose secretion from the SVs of castrated guinea pigs at 4 (9.8 ± 4.2 mg/100 mg) and 8 (4.3 ± 3.7 mg/100 mg) weeks postcastration, as compared with normal adult guinea pigs (54.5 mg/100 mg of SV) 51 . The loss of fructose production may be mediated by reduced expression of SORD since it is known to be an androgen‐regulated gene 52 . Taken together, these data show that age and androgen exposure can affect reproductive physiology in men by directly altering SV fructose production.…”
Section: Fructose: a Key Player In The Physiology Of Male Reproductiv...mentioning
confidence: 99%
See 2 more Smart Citations
“…Ortiz et al detected a significant reduction of fructose secretion from the SVs of castrated guinea pigs at 4 (9.8 ± 4.2 mg/100 mg) and 8 (4.3 ± 3.7 mg/100 mg) weeks postcastration, as compared with normal adult guinea pigs (54.5 mg/100 mg of SV) 51 . The loss of fructose production may be mediated by reduced expression of SORD since it is known to be an androgen‐regulated gene 52 . Taken together, these data show that age and androgen exposure can affect reproductive physiology in men by directly altering SV fructose production.…”
Section: Fructose: a Key Player In The Physiology Of Male Reproductiv...mentioning
confidence: 99%
“…51 The loss of fructose production may be mediated by reduced expression of SORD since it is known to be an androgen-regulated gene. 52 >6.0; sugary breakfast snacks <1.9, 1.9-4.9, >4.9; candy and chocolate <0. the molecular mechanisms involved in pathologies such as PCa, in which androgen dependence, age, and potentially the metabolism of fructose, play an important role.…”
Section: Seminal Vesicles (Svs)mentioning
confidence: 99%
See 1 more Smart Citation
“…This enzyme is located mainly in the cytoplasm and mitochondria of liver, kidney, and seminal vesicle cells, and it is used as an indicator of prostate cancer, as it is highly regulated by androgens. 112 Another dehydrogenase used as a cancer indicator due to its high specificity is l-lactate dehydrogenase (EC 1.1.1.27), widely distributed in human tissues, whose substrates are pyruvate and l-lactate during homolactic fermentation and gluconeogenesis processes, respectively. Overexpression of this dehydrogenase can be a marker for different types of tumors.…”
Section: Dehydrogenases Substratesmentioning
confidence: 99%
“…Two dehydrogenases, specifically, sorbitol dehydrogenase (SDH) and LDH, are used for cancer prognosis [3]. Reports suggested that in prostate cancer [6], and precancerous colorectal neoplasms [7], an abnormal serum concentration of SDH has been observed. Additionally, an enhanced level of SDH can be observed in acute liver damage and parenchymal hepaticdiseases [3].…”
Section: Oxidoreductase-based Diagnostic Tests and As Biosensorsmentioning
confidence: 99%